2020
DOI: 10.1007/s10570-020-03131-8
|View full text |Cite
|
Sign up to set email alerts
|

FTIR analysis of chemical changes in wood induced by steaming and longitudinal compression

Abstract: Pleating is an optimal way to increase bendability of wood used in diverse industrial applications. It results in the excessive buckling of cell walls and modifications of constitutive polymers. However, thoughtful understanding of the physical–chemical mechanisms of that modification process is very limited. The main purpose of the present study was to identify changes in functional groups of wood polymers induced by longitudinal compression. Four types of wood samples prepared from beech and sessile oak (unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
(49 reference statements)
4
20
0
Order By: Relevance
“…Blanchet et al [ 22 ] reported a small negative effect of the vacuum drying process on the mechanical properties of wood, when compared to conventional oven drying. However, noticeable chemical changes in wood polymers as well as its hygroscopic properties because of high-temperature heat treatment were reported by several researchers [ 23 , 24 , 25 , 26 ]. These chemical changes are expected, therefore, to affect other material characteristics including strength and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Blanchet et al [ 22 ] reported a small negative effect of the vacuum drying process on the mechanical properties of wood, when compared to conventional oven drying. However, noticeable chemical changes in wood polymers as well as its hygroscopic properties because of high-temperature heat treatment were reported by several researchers [ 23 , 24 , 25 , 26 ]. These chemical changes are expected, therefore, to affect other material characteristics including strength and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows infrared spectra for the woods that were studied. In comparison with untreated wood, the thermally treated woods showed prominent bands at 1030, 1250, 1650, 2930, and 3400 cm −1 , corresponding to lignin, syringyl units from lignin, cellulose, hemicelluloses, and hydroxyl groups, respectively 41 . These are associated with changes in OH vibrations, mainly from cellulose, but also from aromatic compounds from lignin.…”
Section: Resultsmentioning
confidence: 94%
“…A similar curve for the treated impregnated organoclay/PMFM pulai wood samples revealed the presence of hemicelluloses, cellulose, and lignin. The OH stretching groups on the cellulose molecules and CH stretching vibrations caused the wide peaks between 3600 to 3000 cm -1 , and 3000 to 2800 cm -1 , respectively (Báder et al 2020). The acetyl and ester groups of hemicellulose, or the ester linkage of carboxylic groups of ferulic and p-coumaric acids of lignin or hemicellulose, were ascribed to the significant peak intensities of the impregnated organoclay/PMFM pulai wood samples in the area between 1800 and 1700 cm -1 .…”
Section: Mechanical Propertiesmentioning
confidence: 95%